Community Empowerment through Participatory Mapping of Coastal Waste at Jangkok River Estuary: Pemberdayaan Masyarakat melalui Pemetaan Partisipatif Sampah Pesisir di Muara Sungai Jangkok - Wirahadi Jaya Kusuma; Samsul Hadi; Lira Sari Alfathin; Tisna Apriani; Wiya Zahara Tarwiha; Widi Andriani (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2026)
Coastal waste accumulation at river estuaries poses serious environmental threats, yet community awareness of waste management remains critically low. This community service activity aimed to empower coastal communities at the Jangkok River Estuary, Mataram City, through environmental education and participatory waste mapping. Conducted in 2025, the activity involved 42 participants (89.3% participation rate) comprising fishermen, community members, and local leaders. Methods included interactive educational outreach, line transect waste mapping, group discussions, and pre-test/post-test evaluations. Mapping across 900 m² identified 18.74 kg of total waste, dominated by plastic (68.4%), with the highest density recorded in the estuary zone (0.076 kg/m²). Participant understanding improved significantly from 58.4 to 81.7 (39.9% increase), with participants identifying three primary waste sources and formulating five community-based action recommendations. Environmental education combined with participatory mapping effectively enhanced community awareness and capacity for coastal waste management. These findings provide a foundation for developing a sustainable, community-led waste management plan integrated into local environmental policy.